STRATEGI KOMUNIKASI POLITIK PDI-PERJUANGAN MEMENANGKAN KURSI TERBANYAK PEMILIHAN UMUM 2019 KABUPATEN SUMBAWA - Rizky Alfatiha Suri; Abbyzar Aggasi (Jurnal Komunikasi, 2024)
Legistaive election at 2019 in Sumbawa Regency, PDI-Perjuangan parties won the most seats in the legislative election by winning 6 seats as the parties with the most seats among other’s party factions, various political campaign efforts carried out by party to achieve its goals political possibilities are of course utilized, begining from social media as advice to carryng out political communication to several other political communication strategies to strengthen the mass base of political parties. This research aim to dig into the phenomenom of political communication strategies used by Sumbawa regency PDI-Perjuangan parties in winning the most seats at 2019 Legislative elections. The research method use in this research is descriptive qualitative with a study case type of research, then in this research the data come from inverview with the research subject and explores serveal digital traces new media/social media used by PDI-Perjuangan Sumbawa Regency then processed the data so that conclusions were drawn descriptively. The result of the research of Sumbawa Regency PDI-Perjuangan designed its political communication strategy with the aim of stengthening the mass base by utilizing national nature of parties so that it could enter every element of society, but in using social media the PDI- Perjuangan didn’t utilize these development properly